Faking, forging, counterfeiting: discredited practices at the margins of mimesis - Becker, Daniel; Fischer, Annalisa; Schmitz, Yola; Niehoff, Simone; Sannders, Florencia (transcript, 2018)
Forgeries are an omnipresent part of our culture and closely related to traditional ideas of authenticity, legality, authorship, creativity, and innovation. Based on the concept of mimesis, this volume illustrates how forgeries must be understood as autonomous aesthetic practices - creative acts in themselves - rather than as mere rip-offs of an original work of art. The proceedings bring together research from different scholarly fields. They focus on various mimetic practices such as pseudo-translations, imposters, identity theft, and hoaxes in different artistic and historic contexts. By opening up the scope of the aesthetic implications of fakes, this anthology aims to consolidate forging as an autonomous method of creation.
Literaturangaben
"The international conference "Faking, forging, counterfeiting: discredited practices at the margins of mimesis", held in Autumn 2015 at the Ludwig Maximilian University of Munich ..." (Preface, Seite 8)
Keywords: Konferenzschrift -- Ludwig-Maximilians-Universität -- 2015 -- München; Konferenzschrift -- 2015 -- München; Ästhetik; Nachahmung; Plagiat; Fälschung; Künste